Secondary School Teachers’ Practices and Beliefs About Feedback in Students’ Assessment Processes - Mella-Mella, Flor (2023)
Introduction. Feedback is a fundamental construct of formative evaluation, and a current consensus considers it one of the most powerful strategies for teaching-learning processes. Objective. The study aims to analyze the perception of praxis and conceptions of feedback as essential pillars of formative evaluation in Chile. Methodology. This is a quantitative and non-probabilistic sampling design study in which 100 secondary school teachers participated. The participants were administered a questionnaire, validated through Alpha Cronbach reliability analysis. The data processing was conducted through Jamovi project 2.3. A Likert-type scale was utilized to enable a descriptive analysis of frequencies and items. Results. A high percentage of the participants believed that feedback is a key learning strategy. On the contrary, they presented low percentage values on the use of rubrics and logbooks to provide feedback on students’ progress. Conclusion. Nowadays, teacher training in feedback skills is needed to promote meaningful and formative learning.